Dynamic disruption management in aircraft scheduling (2021)
Aircrafts scheduling is one of the most important steps in an airlineþs operation plan. However, the schedules are not often accomplished as they were initially designed, due to disruptions. This paper provides a modular methodological framework for the disruption management problem focused on the fleet assignment problem for an airline, integrating simulation and optimization strategies to take reactive decisions. Our optimization model proposes an innovative Multicommodity Network Flow Disruption Management (MNFDM) formulation approach, to represent the operations of an airline's fleet and to generate an initial aircraft scheduling. Iteratively, our simulation model generates random disruption realizations and transmits them to the optimization model to develop a recovery plan when they occur...